Teachers lived experiences of teaching and learning in a rural school in the Western Cape - Singh, Marcina (African Perspectives of Research in Teaching & Learning (APORTAL), 2022)
The complexity and bifurcatedness of teaching and learning in the South African education system have been well documented (Singh, 2020; Spaull et al., 2021). However, discussing the intersectionality between race, rurality and inequality as it relates to teaching and learning through a phenomenological lens remains a gap. This article discusses experiences of teaching and learning through the voices of teachers in a small rural town, situated in the Karoo. Using a qualitative approach of semi-structured interviews, the chapter presents insights into the lived experiences of two high school teachers. These responses, through the discussion of teaching and learning, school context, and professional development experiences, are reflected through Paul Ricoeur’s variant of philosophical hermeneutics and justice. This chapter demonstrates that teaching and learning are more than a knowledge exchange in the classroom. It is also about affective support and an unspoken understanding of how the legacy of the past political era(s) is cemented into their daily interactions. The chapter contributes to the literature relating to rural schools as banished spaces in South Africa and positions phenomenological research as a conduit for social justice
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 6 (3) (2022) Special Issue
Keywords: Teachers; Rural schools; School context; Professional development; Inequality; Phenomenology; Education -- Study and teaching; Career development; Educational equalization; Phenomenology; Rural schools -- Western Cape; Education, Rural -- South Africa -- Western Cape